Minimally Invasive Techniques for Nasal Valve Dysfunction: A Systematic Review and Meta-Analysis - Jama, Guled M.; Cainelli, Filippo; Farache Trajano, Luiza; Andrews, Peter J.; Saleh, Hesham (Facial Plastic Surgery, 2025)
Nasal valve dysfunction (NVD) is a prevalent cause of nasal obstruction, significantly impacting quality of life. In recent years, the emergence of office-based interventions has transformed the therapeutic landscape for this condition, offering patients a wider choice and less invasive options compared to traditional surgical methods, yet their comparative safety and efficacy remain to be fully established.A systematic review and meta-analysis were conducted in accordance with Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Four databases (PubMed, Scopus, Cochrane Library, and Ovid) were searched for original studies (2005–2025) assessing minimally invasive treatments for NVD with patient-reported outcomes. Random-effects meta-analyses evaluated changes in Nasal Obstruction Symptom Evaluation (NOSE) and Visual Analog Scale (VAS) scores.Fifteen studies comprising 546 patients were included, evaluating temperature-controlled radiofrequency (TCRF), bioabsorbable implants, intranasal suturing techniques, and nasal valve stenting. TCRF yielded a weighted mean difference (WMD) in NOSE scores of −44.68 (95% confidence interval [CI]: −51.23 to −38.13; p < 0.001), while bioabsorbable implants achieved a WMD of −39.91 (95% CI: −48.53 to −31.29; p < 0.001). Intranasal suturing demonstrated a VAS WMD of −4.36 (95% CI: −4.88 to −3.84; p < 0.001). All interventions surpassed minimal clinically important differences, with adverse events being relatively mild and transient. Improvements were sustained across all modalities over a follow-up period of 3 to 48 months (I2 = 63.9–89.7%).Minimally invasive techniques for NVD demonstrate statistically and clinically significant and durable symptom relief with favorable safety profiles. These interventions may offer viable alternatives to traditional surgical approaches, particularly in select patients seeking reduced morbidity and procedural complexity. Future research should prioritize randomized comparisons and standardized outcome metrics.
Keywords: nasal valve dysfunction; nasal obstruction; minimally invasive techniques; treatment outcome